(untitled) (Journal of EAHIL, 2018)
Finland is undergoing a health and social services reform. This reform will reshape the structure, services and funding of health and social services and establish new counties and transfer new duties to the counties. The aim is to provide people more equal services and even out population level differences in health and well-being, and to curb cost increases. This means a new type of operational environment for the university libraries acting in the hospitals. A survey was conducted at the Kuopio University Hospital to find out the needs of the users. It shows that both library collection resources and information services are needed by academic and hospital staff.